The vibration isolation characteristics of torsion bar spring with negative stiffness structure. (15th November 2022) - Yu, Chuanyun; Fu, Qidi; Zhang, Jianrun; Zhang, Ning
Graphical abstract: Highlights: A quasi-zero-stiffness vibration isolator composed of torsion bar spring and negative stiffness structure is proposed. The proposed nonlinear system is accurately fitted and approximately analytically solved. The advantages of proposed model are analyzed that is larger support capacity and better ride comfort. The proposed model is proved can achieving low-frequency vibration isolation of heavy equipment by finite element method. A static compression test is performed to verify the nonlinear stiffness characteristics of the proposed model. Abstract: Nonlinear stiffness systems are an effective way to achieve low frequency vibration isolation. To improve the support capacity and ride comfort of nonlinear stiffness systems, this paper proposes a quasi-zero stiffness (QZS) vibration isolator composed of the torsion bar spring and negative stiffness structure (NSS) and investigates its vibration isolation characteristics. The influence of the system parameters on the static nonlinear stiffness peculiarities of the vibration isolator is delved. The motion equation of the isolator under the harmonic excitation from the base can be expressed as Helmholtz–Duffing equation due to an offset distance from zero stiffness point to the equilibrium position. The primary resonance response of the QZS system is approximately analytically predicted by Harmonic Balance Method (HBM). The absolute acceleration transmissibility of the QZS system considering the effect of excitation amplitude and system parameters is investigated and compared with the equivalent linear system to evaluate the isolation performance of the nonlinear system. Then, the numerical simulation is investigated and good agreement with theoretical analysis. The validity of the proposed model is verified by finite element method (FEM) and an experiment. Based on the numerical simulation and experiment results, the proposed nonlinear system possesses a better vibration isolation performance of heavy equipment in the low-frequency region.